Genetics and Material Culture Support Repeated Expansions into Paleolithic Eurasia from a Population Hub Out of Africa. (7th April 2022) - Vallini, Leonardo; Marciani, Giulia; Aneli, Serena; Bortolini, Eugenio; Benazzi, Stefano; Pievani, Telmo; Pagani, Luca
Abstract: The population dynamics that followed the Out of Africa (OoA) expansion and the whereabouts of the early migrants before the differentiation that ultimately led to the formation of Oceanian, West and East Eurasian macropopulations have long been debated. Shedding light on these events may, in turn, provide clues to better understand the cultural evolution in Eurasia between 50 and 35 ka. Here, we analyze Eurasian Paleolithic DNA evidence to provide a comprehensive population model and validate it in light of available material culture. Leveraging on our integrated approach we propose the existence of a Eurasian population Hub, where Homo sapiens lived between the OoA and the broader colonization of Eurasia, which was characterized by multiple events of expansion and local extinction. A major population wave out of Hub, of which Ust'Ishim, Bacho Kiro, and Tianyuan are unadmixed representatives, is broadly associated with Initial Upper Paleolithic lithics and populated West and East Eurasia before or around 45 ka, before getting largely extinct in Europe. In this light, we suggest a parsimonious placement of Oase1 as an individual related to Bacho Kiro who experienced additional Neanderthal introgression. Another expansion, started before 38 ka, is broadly associated with Upper Paleolithic industries and repopulated Europe with sporadic admixtures with the previous wave (GoyetQ116-1) and more systematic ones, whereas moving through Siberia (Yana, Mal'ta). Before these events, we also confirm Zlatý Kůň as the most basal human lineage sequenced to date OoA, potentially representing an earlier wave of expansion out of the Hub.